Elevated Plasma Complement C1q Levels Contribute to a Poor Prognosis After Acute Primary Intracerebral Hemorrhage: A Prospective Cohort Study - Wang, Zefan; Wu, Xiaoyu; Yan, Tian; Liu, Ming; Yu, Wenhua; Du, Quan; Hu, Wei; Zheng, Yongke; Zhang, Zuyong; Wang, Keyi; Dong, Xiaoqiao (Frontiers in Immunology, 2022)
Objective: The complement cascade is activated early following intracerebral hemorrhage (ICH) and causes acute brain injury. We intended to explore the effects of plasma complement component 1q (C1q) levels on hemorrhagic severity and functional outcome in ICH patients. Methods: In this prospective cohort study, we collected 101 ICH patients and 101 healthy controls, and measured their plasma C1q levels. Glasgow Coma Scale (GCS) score and hematoma volume were used to assess ICH severity. Poor prognosis was referred to as a Glasgow Outcome Scale (GOS) score of 1-3 at three months following stroke. Multivariate logistic regression model was configured to determine the independent relations of plasma C1q levels to severity and poor prognosis. Under receiver operating characteristic (ROC) curve, prognostic capability of plasma C1q levels was evaluated. Results: There was a significant elevation of plasma C1q levels in patients, as compared to controls (median (percentiles 25th-75th), 225.04 mg/l (156.10-280.15 mg/l) versus 88.18 mg/l (70.12-117.69 mg/l); P<0.001). Plasma C1q levels of patients were independently related to GCS score (t =-3.281, P=0.001) and hematoma volume (t = 2.401, P=0.018), as well as were highly correlated with GOS score at post-stroke 3 months (r=-0.658, P<0.001). Plasma C1q levels were obviously higher in poor prognosis patients than in other remainders (median (percentiles 25th-75th), 278.40 mg/l (213.81-340.05 mg/l) versus 174.69 mg/l (141.21-239.93 mg/l); P<0.001). Under the ROC curve, plasma C1q levels significantly discriminated development of poor prognosis (area under ROC curve 0.795; 95% confidence interval, 0.703–0.869; P<0.001). Using maximum Youden method, plasma C1q levels > 270.11 mg/l distinguished patients at risk of 3-month poor prognosis with 56.52% sensitivity and 94.55% specificity. Meanwhile, the prognostic predictive ability of plasma C1q levels was equivalent to those of GCS score and hematoma volume (both P>0.05). Moreover, plasma C1q levels > 270.11 mg/l independently predicted 3-month poor prognosis (odds ratio, 4.821; 95% confidence interval, 1.211-19.200; P=0.026). Conclusion: Plasma C1q levels are closely related to the illness severity and 3-month poor prognosis of ICH. Hence, complement C1q may play an important role in acute brain injury after ICH and plasma C1q may represent a promising prognostic predictor of ICH.